THE EFFECT OF ATTITUDE TOWARDS SOCIAL MEDIA ADVERTISEMENTS ON BRAND VALUE AND CONSUMER BEHAVIOR - Ballı, Abdullah (Fırat University, 2024)
As consumers begin to spend more time on social networks, social media platforms have become commercial marketing tools. Advertisements for any goods, services or brands, especially on social media platforms, have become effective. Social media advertisements have begun to be very effective on consumers' brand value perception and preferences, and this affects the consumer's thoughts in terms of awareness, loyalty and quality in the context of brand value. As a result, unplanned purchasing behavior has come to the fore. The aim of this study is to investigate the effect of consumers' attitudes towards social media advertisements on brand value and consumer behavior. The data obtained within the scope of the research was obtained by online survey method between 10 March and 30 April 2024. During the data analysis process, SPSS 25.0 and AMOS 26.0 package programs were used within the scope of the research. The results obtained reveal that the attitude of consumers towards social media advertisements has a positive and statistically significant effect on brand value and consumer behavior. In this context, it is seen that social media advertisements play a decisive role in the changes in consumers' perception and this effect indicates a positive relationship between brand value and consumer behavior.

Tüketicilerin sosyal ağlarda daha fazla vakit geçirmeye başlamasıyla birlikte sosyal medya platformları ticari pazarlama aracı haline gelmiştir. Özellikle sosyal medya platformlarında herhangi bir mal, hizmet veya markayla ilgili yapılan reklamlar etkili olmaya başlamıştır. Sosyal medya reklamları tüketicilerin marka değeri algısı ve tercihleri üzerinde oldukça etkili olmaya başlamış ve bu durum tüketicinin marka değeri bağlamında farkındalık, sadakat ve kalite anlamında düşüncelerini etkilemektedir. Bunun sonucunda plansız satın alma davranışı ön plana çıkmıştır. Bu çalışmanın amacı tüketicilerin sosyal medya reklamlarına yönelik tutumlarının marka değeri ve tüketici davranışları üzerindeki etkisini araştırmaktır. Araştırma kapsamında elde edilen veriler, 10 Mart-30 Nisan 2024 tarihleri arasında çevrimiçi anket yöntemiyle elde edilmiştir. Veri analizi sürecinde araştırma kapsamında SPSS 25.0 ve AMOS 26.0 paket programları kullanılmıştır. Elde edilen sonuçlar, tüketicilerin sosyal medya reklamlarına yönelik geliştirdikleri tutumun, marka değeri ve tüketici davranışları üzerinde pozitif ve istatistiksel olarak anlamlı bir etki oluşturduğunu ortaya koymaktadır. Bu bağlamda, sosyal medya reklamlarının tüketicilerin algısındaki değişimlerde belirleyici bir rol oynadığı ve bu etkinin marka değeri ile tüketici davranışları arasında olumlu bir ilişkiye işaret ettiği görülmektedir.
Sosyal Medya Reklamlarına Yönelik Tutumun Marka Değeri ve Tüketici Davranışları Üzerine Etkisi
Keywords: Graph; Social and Multimedia Data; Grafik; Sosyal ve Multimedya Verileri